STRATEGI PENANGANAN SAMPAH DALAM UPAYA PELESTARIAN LINGKUNGAN PANTAI DI DESA BONEATIRO KECAMATAN KAPONTORI KABUPATEN BUTON - Silvia Agnesi Waly; Lely Ersilya; Hasriana; Mawari; Kationo Udin; La Rudi (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2026)
This study aims to analyze waste management strategies for coastal environmental conservation and identify the factors influencing community waste disposal behavior in Boneatiro Village, Kapontori District, Buton Regency. This study employed a descriptive qualitative method with an ecological approach. Data were collected through observation, semi-structured interviews, and documentation, and were analyzed using the Miles and Huberman data analysis model. The findings reveal that waste management strategies include the implementation of the 3R principles (Reduce, Reuse, Recycle), community clean-up activities, public awareness programs, and collaboration between the village government and the local community. SWOT analysis indicates that the implementation has not yet been optimal due to limited public knowledge, the habit of disposing of waste into the sea, and inadequate waste management facilities. Educational level, age, income, and the availability of facilities influence community behavior in waste management. Strengthening environmental education, improving waste management infrastructure, and enhancing community participation are key strategies for achieving sustainable coastal waste management and supporting coastal environmental conservation.